Survey of surgical critical care applicant and program director views on virtual interviews for fellowship training: a Surgical Critical Care Program Directors Society sponsored study - Krista L Kaups; Babak Sarani; James A Zebley; Parker Chang; Ellen Cohn; William Chiu (Trauma Surgery & Acute Care Open)
Background The COVID-19 pandemic forced postgraduate interview processes to move to a virtual platform. There are no studies on the opinions of faculty and applicants regarding this format. The aim of this study was to assess the opinions of surgical critical care (SCC) applicants and program directors regarding the virtual versus in-person interview process.Methods An anonymous survey of the SCC Program Director’s Society members and applicants to the 2019 (in-person) and 2020 (virtual) interview cycles was done. Demographic data and Likert scale based responses were collected using Research Electronic Data Capture.Results Fellowship and program director responses rates were 25% (137/550) and 58% (83/143), respectively. Applicants in the 2020 application cycle attended more interviews. The majority of applicants (57%) and program faculty (67%) strongly liked/liked the virtual interview format but felt an in-person format allows better assessment of the curriculum and culture of the program. Both groups felt that an in-person format allows applicants and faculty to establish rapport better. Only 9% and 16% of SCC program directors wanted a purely virtual or purely in-person interview process, respectively. Applicants were nearly evenly split between preferring a purely in-person versus virtual interviews in the future.Discussion The virtual interview format allows applicants and program directors to screen a larger number of programs and applications. However, the virtual format is less useful than an in-person interview format for describing unique aspects of a training program and for allowing faculty and applicants to establish rapport. Future strategies using both formats may be optimal, but such an approach requires further study.Level of evidence Epidemiologic level IV